The CARMA-NRO Orion survey: filament formation via collision-induced magnetic reconnection—the Stick in Orion A - Kong, Shuo; Ossenkopf-Okada, Volker; Arce, Héctor G.; Bally, John; Sánchez-Monge, Álvaro; McGehee, Peregrine; Suri, Sümeyye; Klessen, Ralf S.; Carpenter, John M.; Lis, Dariusz C.; Nakamura, Fumitaka; Schilke, Peter; et al. (The astrophysical journal, 2021)
A unique filament is identified in the Herschel maps of the Orion A giant molecular cloud. The filament, which we name the Stick, is ruler-straight and at an early evolutionary stage. Transverse position-velocity diagrams show two velocity components closing in on the Stick. The filament shows consecutive rings/forks in C18O (1−0) channel maps, which is reminiscent of structures generated by magnetic reconnection. We propose that the Stick formed via collision-induced magnetic reconnection (CMR). We use the magnetohydrodynamics code Athena to simulate the collision between two diffuse molecular clumps, each carrying an antiparallel magnetic field. The clump collision produces a narrow, straight, dense filament with a factor of >200 increase in density. The production of the dense gas is seven times faster than freefall collapse. The dense filament shows ring/fork-like structures in radiative transfer maps. Cores in the filament are confined by surface magnetic pressure. CMR can be an important dense-gas-producing mechanism in the Galaxy and beyond.
Gesehen am 12.02.2021